ANALISIS PENERAPAN KEBIJAKAN KYOTO PROTOCOL - Muryani Muryani; Citra Pertiwi (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2015)
Increasing competition of good output which interpreted with GDP in developed and developing countries that are members of the G20, have some impact on the degradation of environmental quality. The Production of good output namely GDP cannot be separated from bad output’s production which is CO2. The need for the Kyoto protocol as an environmental policy which has been ratified by the G20 that supposing to control emission levels which can be measured by the measurement of the environmental efficiency of the G20 countries. Apart from the environmental efficiency, efficiency is not the main criterion for making a country to be standard for another country. On the other hand, the performance quality of the environment must also be taken into account. The amount of the cost of environmental policy to maximize environmental efficiency of a country but the environmental performance of the country, state inefficiency in the cost of the policy then the country has not been used in a cost-efficient technology for improving the environmental quality. The approach which has used in this study is a quantitative approach, using Data Envelopment Analysis (DEA). To specify the input and output that is used in determining the environmental efficiency using Malmquist Index. The input and output is processed by looking at differences in productivity and incorporate technological change in its interpretation. It can be concluded that the value of the environmental efficiency of some countries are on the production frontier even if the Kyoto protocol is not implemented, but with the policy of the Kyoto protocol was able to further improve the efficiency of the environment. In some other countries for example Brazil rose from 70.09% to 83.49%, while the Germany states increased by 4.43% in their environmental policy. From some countries evident show that the policy of the Kyoto protocol succeeded in carrying out its role as controlling the growth of emissions in developed and developing countries, especially the G20 members.